(untitled) - Marangoni, Alejandro G. (Hoboken, 2003)
Practical Enzyme Kinetics provides a practical how-to guide for beginning students, technicians, and non-specialists for evaluating enzyme kinetics using common software packages to perform easy enzymatic analyses.
Keywords: Enzyme kinetics.,Models, Chemical